Ureditev delovnega časa med prožnostjo in varnostjo v kolektivnih pogodbah dejavnosti - Senčur Peček, Darja (Delavci in delodajalci, 2018)
The paper analyses the definition of working time, its duration and distribution in 26 collective agreements within the field of economic activities. It can be concluded that collective agreements to a larger extent regulate the institutes which contribute to a more flexible organisation of working hours, but less so to those that contribute to the protection of workers and reconcilliation of professional and family life. The paper highlights the examples of good practice and suggests ideas as how to further regulate them.
Keywords: delovni čas; gospodarska dejavnost; kolektivne pogodbe; pravna ureditev